Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
[tex]x=27,8[/tex]
Explanation:
The equation is
[tex]x^{\dfrac{2}{3}}-5x^{\dfrac{1}{3}}+6=0[/tex]
Let,
[tex]x^{\dfrac{1}{3}}=y[/tex]
So,
[tex]y^2-5y+6=0\\\Rightarrow y=\dfrac{-\left(-5\right)\pm \sqrt{\left(-5\right)^2-4\times 1\times 6}}{2\times 1}\\\Rightarrow y=3,2[/tex]
[tex]x^{\dfrac{1}{3}}=y\\\Rightarrow y^3=x\\\Rightarrow x=3^3\\\Rightarrow x=27[/tex]
[tex]x=2^3\\\Rightarrow x=8[/tex]
Hence, [tex]x=27,8[/tex].
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.